Because
![\frac{f(x)}{x-3} = 2x^{2} + 10x - 1](https://tex.z-dn.net/?f=%20%5Cfrac%7Bf%28x%29%7D%7Bx-3%7D%20%3D%202x%5E%7B2%7D%20%2B%2010x%20-%201)
therefore
f(x) = (x-3)(2x² + 10x - 1) + k, where k = constant.
Because f(3) = 4, therefore k =4.
The polynomial is
f(x) = 2x³ + 10x² - x - 6x² - 30x + 3 + 4
= 2x³ + 4x² - 31x + 7
Answer: f(x) = 2x³ + 4x² - 31x + 7
Answer:
I am not getting your question .
Hello!
A cube has 6 faces which is the shape of a square, all corners are 90 degrees and it’s x^3
the lateral area and total area of regular pyramid with a square base is 130